Analysis of Factors Affecting Medication Adherence in Tuberculosis Patients at Puskesmas Medan Area Selatan - Widia Astuti Tanjung; Ristika Julianty Singarimbun (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Tuberculosis (TB) remains a major public health challenge in Indonesia, with approximately 1,090,000 cases reported annually. Achieving the national TB elimination target by 2030 requires optimal treatment adherence; however, medication non-adherence continues to hinder treatment success and disease control. This study aimed to identify factors influencing medication adherence among pulmonary TB patients at Puskesmas Medan Area Selatan. Methods: A cross-sectional analytic study was conducted from January to March 2025 involving pulmonary TB patients registered under the Directly Observed Treatment Short-course (DOTS) program. A total of 87 respondents were recruited using consecutive sampling based on the following inclusion criteria: confirmed pulmonary TB diagnosis, undergoing at least one month of treatment, and willingness to participate. Data were collected using structured questionnaires assessing six independent variables: patient knowledge, family support, healthcare service quality, drug side effects, the role of treatment supervisors (PMO), and socioeconomic status. Medication adherence was measured using the Morisky Medication Adherence Scale-8 (MMAS-8). Binary logistic regression analysis was performed using SPSS version 26.0. Results: Among the respondents, 62.1% demonstrated good medication adherence. Bivariate analysis revealed significant associations between adherence and patient knowledge (p = 0.001; OR = 4.87; 95% CI: 1.89–12.53), family support (p = 0.003; OR = 3.94; 95% CI: 1.56–9.94), healthcare service quality (p = 0.021; OR = 2.87; 95% CI: 1.17–7.03), and drug side effects (p = 0.038; OR = 2.41; 95% CI: 1.05–5.51). Multivariate logistic regression identified patient knowledge as the most dominant factor influencing adherence (Adjusted OR = 5.12; 95% CI: 1.91–13.70; p = 0.001), followed by family support (AOR = 3.78; 95% CI: 1.43–9.98; p = 0.007). Conclusion: Patient knowledge is the strongest determinant of medication adherence among TB patients at Puskesmas Medan Area Selatan. Strengthening structured health education interventions and promoting family-centered support strategies are essential to enhance treatment adherence and accelerate progress toward Indonesia’s TB elimination target by 2030.